2016
DOI: 10.1016/j.envpol.2016.08.071
|View full text |Cite
|
Sign up to set email alerts
|

On the association between outdoor PM2.5 concentration and the seasonality of tuberculosis for Beijing and Hong Kong

Abstract: 31Tuberculosis (TB) is still a serious public health problem in various countries. One of the long-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 52 publications
7
62
1
1
Order By: Relevance
“…In addition, the diagnosis and reporting of TB also require times that can cause a delay. Thus, if the increased concentration of ambient air pollutants contributes to TB, extra time is required for an infected individual to develop active disease, be diagnosed, and finally be reported by a health care institution (Murray et al, 2011;You et al, 2016). This type of lag was assumed to be over 2 months because the median time interval between infection and active disease was 7 weeks (Naranbat et al, 2009).…”
Section: Statistics Analysismentioning
confidence: 99%
“…In addition, the diagnosis and reporting of TB also require times that can cause a delay. Thus, if the increased concentration of ambient air pollutants contributes to TB, extra time is required for an infected individual to develop active disease, be diagnosed, and finally be reported by a health care institution (Murray et al, 2011;You et al, 2016). This type of lag was assumed to be over 2 months because the median time interval between infection and active disease was 7 weeks (Naranbat et al, 2009).…”
Section: Statistics Analysismentioning
confidence: 99%
“…We found hours of sunlight, absolute humidity and average temperature were significantly associated with TB incidence at a lag of six months. The association between sunlight and TB incidence with a lag of six months, was similarly demonstrated in studies from the UK, China, and Peru (13,15,16). To…”
Section: Mixed-effect Linear Model: Association Between Explanatory Vmentioning
confidence: 62%
“…A study from Wingfield et al in Peru demonstrated a mid-winter peak in Vitamin D deficiency followed by a peak in tuberculin skin test positivity 6 weeks later and a peak in symptoms 9 weeks after that. (13) There have been few environmental epidemiological studies analyzing the seasonality of TB with respect to climate variables, but when hours of sunlight were included in the analysis, most showed a clear association (8,(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The decentralized application of the gasification technology in modern cities means the proximity of gasification systems to the public and residential communities. This imposes strict requirements on its emission control and management because elevated outdoor particle concentrations pose a potential health concern, especially for fine particles such as PM 2.5 that could penetrate deeply into the human respiratory system (Happo et al, 2013;Jalava et al, 2012;Moller and Loft, 2010;Naeher et al, 2007;You et al, 2016a). Our recent study also showed that elevated outdoor PM 2.5 may lead to increased household energy use and corresponding household carbon footprint by changing the energy utilization mode (e.g., more air-conditioner and purifier use) (You et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%